"Gender Quotas" in French and Italian Public Law: A Tale of Two Overlapping and Then Diverging Trajectories. Issue 6 (6th November 2018) - Möschel, Mathias
Abstract: This Article compares the French and Italian experiences with gender quotas—understood as mechanisms intended to increase women's participation in public life, including but not limited to, the reservation of seats in certain positions and the modulation of electoral lists— in public entities such as legislative and executive bodies (including political parties), the judiciary, and public universities. The comparison between France and Italy demonstrates that even between two countries whose constitutional history and trajectory with regard to gender quotas has been portrayed as being essentially identical, a closer analysis of the recent developments in both countries' constitutional and administrative case law shows a slightly more nuanced picture. Using Rodolfo Sacco's approach of legal formants, this Article argues that the difference stems mainly from the different attitude and interpretation of equality by the judicial formant.